A STUDY OF STUDENTS’ SENSE OF LEARNING COMMUNITY IN ONLINE ENVIRONMENTS - Shea, Peter (Online Learning, 2006)
This paper looks first at some of the often unspoken epistemological, philosophical, and theoretical assumptions that are foundational to student-centered, interactive online pedagogical models. It is argued that these foundational assumptions point to the importance of learning community in the effectiveness of online learning environments. Next, a recent study of 2314 online students across thirty-two college campuses is presented. This study reports on learners’ sense of community and it is concluded through factor and regression analysis that elements of the Community of Inquiry model —specifically learners’ recognition of effective “directed facilitation” and effective instructional design and organization on the part of their instructor contributes to their sense of shared purpose, trust, connectedness, and learning—core elements of a community of learners. Gender also appears to play a small role in students’ sense of learning community with female students reporting higher levels than their male classmates. Implications for online learning environments design are discussed.